APPLICATION OF INTERNET OF THINGS (IOT) IN MODERN LIVESTOCK MANAGEMENT IN NEW ZEALAND - Dina Destari; Raul Gomez; Bruna Costa; Ardi Azhar Nampira (Techno Agriculturae Studium of Research, 2025)
This study examines the application of Internet of Things (IoT) technology in modern livestock management in New Zealand. The background of this research is based on the need to increase productivity, efficiency, and sustainability in the increasingly competitive livestock sector. The purpose of the study is to explore the benefits of applying IoT in livestock health monitoring, feed management, as well as the impact of this technology on the environment and sustainability. The research method used is descriptive-qualitative with data collection through interviews, field observations, and secondary data analysis. The results show that the adoption of IoT in large farms increases productivity by up to 20% and reduces operational costs through more efficient feed management. The study also found that infrastructure challenges are a hindrance to IoT adoption in small and medium-sized farms. The conclusion of the study is that IoT has the potential to be a key solution to improve efficiency and sustainability in the livestock sector, but infrastructure support and training are urgently needed to accelerate its adoption across sectors.